PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI - Reza Rinova; Fajar Gustiawaty Dewi (Jurnal Akuntansi dan Keuangan (JAK), 2019)
Expansion of regions is aimed to prosper the community. In 2018 as many as 314 proposals for expansions could not be approved by the Minister of Home Affairs because the impact was not in line with expectations. This study aims to see the direct effect of the financial performance of the newly formed government regions on economic growth. Expansion area are divided into two forms, namely the old expansion area and the new expansion area. The financial performance of the local government is measured using the ratio of decentralization rates, regional dependency ratios, and the effectiveness of LGR (Locally-Generated Revenue) ratios. Population in this study is all the expansion areas of districts/cities on the island of Sumatera. Time-series secondary data year 2013-2017 covering regional original income, total regional income, transfer income, regional original income budget, and realization of Gross Regional Domestic Product (GRDP) were used. Using SPSS tool, the results shows that the ratio of the degree of decentralization has a negative effect on economic growth. Furthermore, regional dependency ratios do not affect economic growth. The LGR effectiveness ratio has a positive effect on economic growth.